2014
DOI: 10.3389/fmicb.2014.00246
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Zymomonas mobilis physiology and stress responses by quantitative proteomics and transcriptomics

Abstract: Zymomonas mobilis is an excellent ethanologenic bacterium. Biomass pretreatment and saccharification provides access to simple sugars, but also produces inhibitors such as acetate and furfural. Our previous work has identified and confirmed the genetic change of a 1.5-kb deletion in the sodium acetate tolerant Z. mobilis mutant (AcR) leading to constitutively elevated expression of a sodium proton antiporter encoding gene nhaA, which contributes to the sodium acetate tolerance of AcR mutant. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…2 Mb, Seo et al ., ). The genome annotation has been improved recently (Yang et al ., ), which greatly assists in the accumulation of Z. mobilis systems biology data, especially the microarray‐based transcriptomic datasets of different strains grown under different conditions (Yang et al ., , , , ,b; Hayashi et al ., ; He et al ., ,b; Jeon et al ., ; Skerker et al ., ; Yi et al ., ; Zhang et al ., ). The availability of several other Z. mobilis genomes, such as CP4, NCIMB 11163, ATCC 29191, ATCC 29192, ATCC 10988 and ZM4 mutants of ATCC 31822 and ATCC 31823 (Kouvelis et al ., , , , ; Peralta‐Yahya and Keasling, ; Pappas et al ., ; Smith and Liao, ; Desiniotis et al ., ; Zhao et al ., , ) and other strains in the sequencing pipeline makes comparative genomics research practical.…”
Section: Classical Genetics Tools and Emerging Technologymentioning
confidence: 99%
“…2 Mb, Seo et al ., ). The genome annotation has been improved recently (Yang et al ., ), which greatly assists in the accumulation of Z. mobilis systems biology data, especially the microarray‐based transcriptomic datasets of different strains grown under different conditions (Yang et al ., , , , ,b; Hayashi et al ., ; He et al ., ,b; Jeon et al ., ; Skerker et al ., ; Yi et al ., ; Zhang et al ., ). The availability of several other Z. mobilis genomes, such as CP4, NCIMB 11163, ATCC 29191, ATCC 29192, ATCC 10988 and ZM4 mutants of ATCC 31822 and ATCC 31823 (Kouvelis et al ., , , , ; Peralta‐Yahya and Keasling, ; Pappas et al ., ; Smith and Liao, ; Desiniotis et al ., ; Zhao et al ., , ) and other strains in the sequencing pipeline makes comparative genomics research practical.…”
Section: Classical Genetics Tools and Emerging Technologymentioning
confidence: 99%
“…For example, transcriptomic profiles of Z. mobilis wild-type strain ZM4 or its xyloseutilizing derivative 8b in response to furfural, acetate, or phenolic aldehyde inhibitors (4-hydroxybenzaldehyde, syringaldehyde, and vanillin) have been investigated (He et al 2012;Yang et al 2014a;Yi et al 2015). In addition, integrated proteomic and transcriptomic approaches were used to understand the molecular mechanism of an acetate-tolerant strain (Yang et al 2014c). All these studies demonstrated that multiple-gene regulation is responsive for the inhibitor tolerance in Z. mobilis involving in carbohydrate metabolism, DNA replication, recombination and repair, transcriptional regulation, and universal stress responses.…”
Section: Robustness Improvement By Reverse Genetics Approachesmentioning
confidence: 99%
“…Cells were resuspended with test medium. Bioscreen C assays were carried out as described previously [16,[27][28][29][30][31]…”
Section: Resultsmentioning
confidence: 99%